O Pensamento reflexivo e a formação identitária do aluno de inglês no ensino médio - Santana, Mara Lúcia (2006)
This study is inserted in the Language and Education research line and this research aims at investigating the developing of the reflexive thought of students of the secondary education, in classroom of English language, on the basis of a course designed from a an available textbook in the market, and to observe the possible consequence of it in the construction and reconstruction of the identity. The theoretical background that supports this research is a case study guided by the questions of research a) how to develop a reflexive process with students of the secondary education from an available textbook in the market, b) what perceptions the students has of itself like the apprentices of English language in the beginning of the course, c) what perceptions the students has of itself like the apprentices of English language in the end of the course and d) which are the repercussion of the course in the construction and reconstruction of the identity. The theoretical fundamentation that supports this research is guided byVygotsky (1934/2000, 1998) and his socio theory cultural; Bakhtin (1995, 2000) and his teachings about the language and its predominant paper in the communication between human been; Morin (1996, 2001a, 2001b) defending new forms of think the social one as a whole and not more fragmented; Dewey (1938, 1959) and his studies about the reflexive thought; ; Soares (2004), Kleiman (2002) e David (2003) and their contributions about letramento, Moita Lopes (19996), Hall (2000), Tavares (1996) e Wenger (1998) and its collaborations about the identity. The results of the work carried out indicates that the diverse experiences lived throughout the course make possible to the same ones to perceive themselves as pupils of English language with differentiated performance of previous years as well as had learned how to share and joins the knowledge with the colleague creating a space of mutual collaborations